PENGARUH KENYAMANAN RUANG PULIK, PELAYANAN DAN FASILITAS TAMAN JAYAWIJYA MOJOSONGGO DI SURAKARTA TERHADAP KEPUASAN WISATAWAN - Bartolomeus Herawan Mintardjo (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
The aim of this study is to know the influence of public space conveniences (X1), services (X2), and facilities (X3) in Jayawijaya Park on tourist satisfaction (Y). Jayawijaya Park is one of the tourist destinations developed by Local Government.. The type of this research is quantitative, in which the visitors of Jayawijaya Park become the population. Data collection techniques used are questionnaires, interviews, documentation, and literature study. The sample used was 100 respondents (Convenience Sampling) that encountered Jayawijaya Park on February 2023. The data analysis technique used is multiple linear regression which passed the classic assumption with the equation Y= -3,045 + 0,210X1 + 0,177X2 + 0,206X3 + e result. Tested by partial test (test-t), simultaneous test (test-F), and coefficient of determination test using SPSS 26 version showed positive influence and also effect of Variable X on Y is 65,6%. This research can bring knowledge or information to the readers, managers, or visitors of Jayawijaya Park and even reference for the next research. This research also can be a reference and evaluation material for the managers to upgrade and maintain the conveniences of public spaces, services, and facilities to create a sustainable tourist area that leads to positive feedback from the visitors.